1998
DOI: 10.1111/j.1151-2916.1998.tb02725.x
|View full text |Cite
|
Sign up to set email alerts
|

New Preparation Method of Low‐Temperature‐Sinterable Perovskite 0.9Pb(Mg1/3Nb2/3)O3‐0.1PbTiO3 Powder and Its Dielectric Properties

Abstract: A relaxor ferroelectric material, 0.9Pb(Mg 1/3 Nb 2/3 )O 3 -0.1PbTiO 3 (0.9PMN-0.1PT) with a pyrochlore-free phase, was prepared by using one-step calcination in the present study. The 0.9PMN-0.1PT powder with the pure perovskite phase was prepared successfully from a mixture of the PMN precursor and the crystalline PT by heating for 2 h at temperatures ≥750°C. The PMN precursor was synthesized by adding an aqueous Mg(NO 3 ) 2 solution, rather than MgO, to the alcoholic slurry of PbO and Nb 2 O 5 . The 0.9PMN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Studies showed that the Mg 2+ reactivity and distribution was critical to the perovskite phase formation [24,25]. With this principle, the PMN pervoskite powder was prepared successfully via a single-step calcination by replacing MgO with Mg(NO 3 ) 2 [12].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies showed that the Mg 2+ reactivity and distribution was critical to the perovskite phase formation [24,25]. With this principle, the PMN pervoskite powder was prepared successfully via a single-step calcination by replacing MgO with Mg(NO 3 ) 2 [12].…”
Section: Resultsmentioning
confidence: 99%
“…1 -4 at.% of SrO doping would result in the low sintering temperature of 800 -900 -C [17]. Using the PMN powder made from Mg(NO 3 ) 2 mixing method, the sintering temperature was decreased to 900 -C [12]. Directly pressing the columbite phase (MgNb 2 O 6 ) and PbO into green bodies and then reactively sintering the green bodies reduced the total processing steps of PMN/PMN -PT ceramics into two steps of ball-millings, one step of calcination, and one step of sintering [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swartz and Shrout [8] obtained PMN in high yield by using a columbite route, in which MgO and Nb 2 O 5 are first reacted to synthesize columbite phase (MgNb 2 O 6 ), followed by the reaction with PbO to synthesize perovskite phase. Several other processing methods have also been able to eliminate the formation of pyrochlore phase in powders, including sol-gel, solution processes, co-precipitation, soft mechanochemical pulverization, Mg(NO 3 ) 2 mixing, molten salt method, and thermal spray methods [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This method was widely adopted in both the industry and the scientific research due to its relatively less stringent requirement to the raw materials and equipment. Several other processing methods have also been found that were able to eliminate the formation of pyrochlore phase in powders, including sol–gel, 3–6 solution processes, 7–9 co‐precipitation, 10 soft mechanochemical pulverization, 11 Mg(NO 3 ) 2 mixing, 12 and thermal spray methods 13 . A molten salt method has also been shown to be able to produce single‐phase perovskite PMN–PT powders 14 …”
Section: Introductionmentioning
confidence: 99%